2018
DOI: 10.11604/pamj.2018.31.21.15120
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards rabies prevention among residents of Abuja municipal area council, Federal Capital Territory, Nigeria

Abstract: IntroductionRabies is a fatal neglected zoonosis killing 55,000 people worldwide annually. It is endemic in Nigeria with 10,000 people exposed annually through dog-bites. To inform adequate intervention due to the rise in reported dog-bite cases, we assessed knowledge, attitudes and practices (KAP).MethodsWe carried out a cross-sectional study among 224 residents in Abuja Municipal Area Council. We used structured questionnaires to collect data on sociodemographic characteristics, knowledge and attitudes on ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 9 publications
8
18
2
1
Order By: Relevance
“…While worrisome, these observations were not unique to our study. Similar findings were observed elsewhere on the African continent where several studies also found that the lack of knowledge of post exposure treatment was one of the most significant deficiencies in the knowledge profile of respondents [ 15 18 , 20 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…While worrisome, these observations were not unique to our study. Similar findings were observed elsewhere on the African continent where several studies also found that the lack of knowledge of post exposure treatment was one of the most significant deficiencies in the knowledge profile of respondents [ 15 18 , 20 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 87%
“…While respondents in our study were never specifically asked whether they had their pets vaccinated at any point in time, these observations would suggest that approximately 43% of the owned dog population should theoretically have received their annual vaccination against rabies every year. Assuming this to be accurate, the results would be similar to findings from Uganda [ 17 ] and Kenya [ 21 ] where a low percentage of respondents (between 35% and 43%) reported having their pets vaccinated against rabies, and in contradiction to findings from Nigeria [ 18 ], Ethiopia [ 19 ] and Rwanda [ 20 ] where a much higher percentage of respondents (between 74% and 94%) reported having their pets vaccinated against rabies. Furthermore, this speculative vaccination coverage in the HMP (30%) is well below the recommended vaccination coverage of 70% [ 1 ], which could explain the persistence of the disease in the province.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These results indicate that people who are older and have higher income or good health status are more likely to take measures to prevent COVID-19, which is consistent with previous findings [ 67 ]. Additionally, education and marital status were significant predictors in the existing literature; for example, in one study [ 71 ], the odds of having accurate knowledge of malaria increased as individuals’ educational levels increased, and unmarried people were found to be more likely to have positive attitudes toward rabies prevention than married people [ 41 ]. However, these variables were not significant in this study, perhaps due to the different social contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Authorities are generally implementing additional measures to improve the level of disease knowledge among the public, with the aim of changing the attitudes of citizens toward public health prevention [ 40 ]. For example, disease knowledge can change attitudes and practices toward rabies prevention [ 41 ], levels of oncological knowledge had an impact on individuals’ decisions to consent to particular medical procedures [ 42 ], and higher public health knowledge was positively associated with more frequent handwashing [ 14 ].…”
Section: Introductionmentioning
confidence: 99%